The design of performance measurement for balanced scorecard method integrated with six sigma (A case study in PT Jasuindo Tiga Perkasa, Tbk.) - Rizka Herjayanti; Rovila El-Maghviroh (The Indonesian Accounting Review, 2015)
The purpose of this study is to design a Balanced Scorecard performance measurement that is integrated with Six Sigma methods in PT Jasuindo Tiga Perkasa, Tbk. Balanced Scorecard is a performance measurement method that includes the measurement of four perspectives; financial perspective and the other three non-financial perspectives (customer perspective, internal business processes perspective, and learning and growth perspective). This measurement method is integrated with DMAIC process (definition, measurement, analysis, improvement, control). Analysis technique is to identify the vision, mission, objectives, SWOT analysis and company strategy. Based on the measurement using key performance indicators of each perspective, the analysis is done in case of the decrease in performance, and focuses on finding control and solution to improve the performance. This study also measures the level of Six Sigma, where the company managed to achieve sigma level of 6.20, or 99.999869%. The re-sults obtained from the measurement are in accordance with the key performance indi-cators in which 1) there is an increase in financial perspective 2) there is a decrease in customer perspective, 3) there is an increase in internal business process perspective, and 4) there is a decrease in learning and growth perspective.